Crisis, institutional innovation and change management: Thoughts from the Greek case - VLADOS, Charis; CHATZINIKOLAOU, Dimos (Journal of Economics and Political Economy, 2019)
Abstract. This article explores how the current global crisis and restructuring of global capitalism is related to innovation, in broad terms, and change management. The aim is to understand this relation by first presenting a synopsis of the approaches to the crisis of the Greek socioeconomic system, second focusing on the concept of innovation in institutional terms, and third examining the change management mechanisms that seem useful for the articulation of public economic policy in Stra.Tech.Man terms (synthesis of Strategy-Technology-Management). We suggest that to overcome actual structural crises -such as the Greek socioeconomic crisis- the implementation and valorization of well balanced and effectively implemented sets of institutional innovations is crucial, provided that integrated public policy change management mechanisms are in place. Keywords. Globalization restructuring, Greek crisis, Structural socioeconomic crisis, Institutional innovation, Public policy reform, Change management, Stra.Tech.Man analysis. JEL. O10, B52, O31.